Management of Nutmeg Pulp Waste in Lilibooi Village, West Leihitu District, Central Maluku Regency - Sophia Grace Sipahelut; John Alfred Patty (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
This community-empowerment activity was conducted in Lilibooi Village, West Leihitu District, Central Maluku Regency. The object of this activity was the nutmeg female farmers. This activity aimed at improving the people’s knowledge and skills in utilizing the nutmeg pulp waste by processing it into the nutmeg sheet jam. Counselling, training, mentoring, and evaluating activities were the methods used in this program. The counseling activities ran very well and were considered highly beneficial. The participants’ participation and enthusiasm level were very good. The transfer of science and knowledge related to the nutrient contents, potentials, and nutmeg pulp processing technology encouraged the community to realize the importance of the diversification of nutmeg pulp processed products. The training activities aimed at improving the skills of female farmer groups in processing the nutmeg sheet jam. The community service team first demonstrated the nutmeg sheet jam processing before the participants were requested to practice the processing technique. In this training, the nutmeg female farmer group was also given the nutmeg sheet jam processing equipment. Mentoring activities were further provided to the participants to ensure that they were adequately skillful to process the nutmeg sheet jam. The evaluation result, ranging from like to really like scale, was conducted with organoleptic testing to the level of flavor preference, color, aroma, and texture from nutmeg sheet jam.